Вы находитесь на странице: 1из 14

SUCCESSIVE DIFFERENTIATION:

LEIBNITZ'S THEOREM
OBJECTIVES
At the end of this session, you will be able to understand:
Definition
nth Differential Coefficient of Standard Functions
Leibnitzs Theorem
DIFFERENTIATION: If y = f (x) be a differentiable function of x, then

dy
= f ' ( x) is called the first
dx

differential coefficient of y w.r.t x.


Hence, differentiating both side w.r.t. x, we have
d dy d
= f ' ( x ) = f '' ( x ) .
dx dx dx
d2 y
d2 y
d dy
Let be represented by 2 ; then
= f '' ( x )
dx
dx 2
dx dx
2
d3 y
d3 y
d d y
Similarly 2 is represented by
; ie 3 = f ''' ( x ) and so on
dx3
dx
dx dx
dy d 2 y d 3 y
dn y
The expressions
, 2 , 3 ,....... n are called the first, second, third, .....nth differendx dx d x
dx
tial coefficient of y.

These function are usually written as


y',y'',y''',......y n or y1 ,y 2 y3 ........................y n and also Dy, D 2 y, D 3 y,.......D n y.

nth DIFFERENTIAL COEFFICIENT OF STANDARD FUNCTION:


(i) Differential Coefficient of

xm :

If y = x m , then y1 = mx m 1 ;
y 2 = m(m 1) x m 2 ; y3 = m(m 1)(m 2) x m3 and so on
In general, y n = m(m 1)(m 2)(m 3).........................(m n + 1) x m n ;
1

Note: If m be a positive integer, we have

y n = 1.2.3............m = m !;
Hence Dn ( x m ) = m( m 1)(m 2)(m 3)............(m n + 1) x m n
(ii) Differential Coefficient of

(ax + b) m :

If y = (ax+b)m , then y1 = am(ax + b) m 1 ;


y2 = a 2 m(m 1)(ax + b) x m 2 ; y3 = a 3 m(m 1)(m 2)(ax + b) x m3 and so on.
In general yn = a n m(m 1)(m 2)(m 3)............(m n + 1)(ax + b) x m n
[Note: In the first differentiation, the last term in it is (m 1 + 1) ; in the second differentiation it is
(m 1) i.e. (m 2 + 1) ;in the third differentiation it is (m 2) i.e. (m 3 + 1) .So the nth differentiation it
will be (m n + 1) .]
Hence D (ax + b)m = a n m(m 1)(m 2)(m 3)............(m n + 1)(ax + b) m n
m!
or D(ax + b) m =
a n (ax + b) m n
(m n)!
In case m is negative integer,let m p, where p is positive integer, then
D(ax + b) p = a n ( p )( p 1)( p 2)....................[ p ( n 1)](ax + b) p n
= a n (1) n p( p + 1)( p + 2)....................[( p n + 1)](ax + b) p n
( p n + 1)! n
= (1) n
a (ax + b) p n
( p 1)!
Note1. If m = n.then D n (ax + b) p = a n !
Note2. If m = 1, we have D n (ax + b)1 = (1)(1 1)................(1 n + 1)a n (ax + b) 1 n
(1) n 1.2.3...........na n (ax + b) 1 n = (1) n n !a n (ax + b) 1 n =
(iii) Differential Coefficient of

If y = log(ax + b), then


y2 =

(1) n n !a n
.
(ax + b) n +1

(ax + b) :
y1 =

a
a(0!)
= a (ax + b) 1 =
(ax + b)
(ax + b)

a 2 .1
a 2 .(1!)
a3 .2
a 3 .(2!)
=

.
=
=

.
y
3
(ax + b) 2
(ax + b) 2
(ax + b)3
(ax + b)3

a4 2.3
a 4 .(3!)
3
=
and so on.
y4 =

(
1)
.
(ax + b)4
(ax + b) 4

In general,

a n .(n 1)!
yn = (1) .
(ax + b) n
n 1

Hence D n log(ax + b) = (1) n 1 .

a n .(n 1)!
.
(ax + b) n

(1) n 1 (n 1)!
Note: D log x =
.
xn
n

(iv) Differential Coefficient of

a bx :

If y = a bx , then y1 = ba bx log a, y2 = b 2 a bx (log a ) 2 .


y3 = b3 a bx (log a )3 , and so no.
In general, yn = b n a bx (log a ) n ,
Hence D n .a bx = b n a bx (log e a ) n .
(v) Differential Coefficient of

e ax :

If y = eax , then
y1 = ae ax ,y2 = a 2 e ax ,y3 = a 3 e ax , y4 = a 4 e ax and so on.
In general, yn = a n e ax , Hence D n e ax = a n e ax .
(vi) Differential Coefficient of

sin(ax + b) :

If y = sin( ax + b), then

y1 = a cos(ax + b) = a sin + (ax + b)


2

+ (ax + b) , and so on.


y2 = a 2 cos(ax + b) = a 2 sin
2

In General,y1 = a n sin ax + b + n .
2

Hence, D n (ax + b) = a n sin ax + b + n


2

n
Note: D n sin x = sin x +
2

(vii) Differential Coefficient of

cos(ax + b) :

If y = cos(ax + b), then

y1 = a sin( ax + b) = a cos + ax + b
2

+ ax + b , and so on
y2 = a 2 sin + ax + b = a 2 cos
2

In general, yn = a n cos ax + b + n .
2

Hence, D n cos x (ax + b) = a n cos ax + b + n .


2

Note : D n cos x = cos x + n .


2

(viii) Differential Coefficient of

e ax sin(bx + c) and e ax cos(bx + c) :

y = e ax sin(bx + c), then

If

y1 = e ax sin(bx + c) + be ax cos(bx + c) = e ax [ a sin(bx + c) + b cos(bx + c)]


Putting a = r cos and b = r sin , we get
b
y1 = re ax sin(bx + c + ), where r 2 = a 2 + b 2 and = tan 1 ,
a
similary, y1 = r 2 e ax sin(bx + c + 2 ), and so on.
Hence, D n eax sin(bx + c) = r n e ax sin(bx + c + n )
1
2 2

b
where r = (a + b ) and = tan 1 .
a
Similarly, D n e ax cos(bx + c) = r n e ax cos(bx + c + n )
2

b
where r = (a 2 + b 2 ) 2 and = tan 1 .
a
Example. Find the n th derivative of e ax sin bx cos cx.
Solution.

1 ax
e (2sin bx cos cx)
2
1
1
= e ax [sin(bx + cx) + sin(bx cx)] = [eax sin(b + c)x + eax sin(b c) x].
2
2

b
Now D n e ax sin(bx + cx) = (b2 + c2 )n / 2 eax sin bx + c + n tan 1
a

Let y = e ax sin bx cos cx =

{a 2 + (b + c)2 }n / 2 e ax sin { (b + c)x + n tan 1 (b + c) / a}

1
yn =
n
/
2
(
b
c
)


2 + {a 2 (b c)2 } eax sin (b c)x + n tan 1

a

Example. If

y = e ax sin bx, proved that y 2 2ay1 + ( a 2 + b 2 ) y = 0.

Solution.

Let y = e ax sin bx,

y1 = ae ax sin bx + be ax cos bx

and y2 = a 2 e ax sin bx + 2abe ax b 2 e ax sin bx


Also

2ay1 = 2a 2 e ax sin bx 2abe ax cos bx

and (a 2 + b 2 ) y = a 2 e ax sin bx + b 2 e ax sin bx


Adding (1),(2)and (3), we get

...............(1)
...............(2)
.................(3)

y 2 - 2ay1 + (a 2 + b 2 ) y = 0
LEIBNITZ'S THEOREM:

The find nth differential coefficient of two function of x


If u and v are any two functions of x such that all their desired differential coefficients exist, then the nth
differential coefficient of their product is given by

D n (uv) = ( D n u ).v + n c1 D n 1u.Dv + n c2 D n 1u.D 2 v + ....... + n cr D n r n.D r v + ...... + uD n v.


or
D n (uv) = ( D n u ).v + nD n 1u.Dv +

n(n 1) n 2 2
D uD v + ............. + nDuD n 1v + uDv.
2!

Proof.

Let y = uv, we have


Dy (uv) = ( D n u ) = ( Du ).v + u.Dv
From (1) we see that the theorem is true for n = 1.

........ ......(1)

Now assume that the theorem is true for a particular value of n,we have
D n (uv) = ( D n u ).v + nc1 D n 1u.Dv + nc 2 D n 2 u.D 2 v + ....... + n cr D n r u.D r v
+ nr +1 D n r 1uD r +1v + ...... + uD n v

............(2)

Differentiating both siede of (2) w,r,t,x, we get


D n +1 (uv) = ( D n +1u ).v + D n uDv + ( nc1 D n u.Dv + nc1 D n 1u.D 2 v )

+ ( nc 2 D n 1u.D 2 v + nc 2 D n 2 u.D 3 v ) + ..... + ( ncr D n r +1u.D r v + ncr D n r u.D r +1v )


+ ( ncr +1 D n r u.D r +1v + ncr +1 D n r 1u.D r + 2 v ) + ..... + ( DuD n v + u.D r +1v ) .

Rearranging the term, we get


D n +1 (uv) = ( D n +1u ).v + (1 + nc1 ) + ( D n uDv) + (nc1 + nc 2 ) D n 1u.D 2 v +
..... + (ncr + nr +1 )( D n r u.D r +1v) + ...... + uD n +1v

...(3)

But we know that n c1 + n cr +1 = n +1 cr +1 . Therefore


1 + n c1 = n c0 + n c1 = n +1 c1 ,

c1 + n c2 = n +1 c2, and so on.

Hence(3) gives
D n +1 (uv) = ( D n +1u ).v + n +1 c1 ( D n u ).Dv + n +1 c2 ( D n 1u ).( D 2 v ) + .........
..... + n +1 cr +1 D n r u.D r +1v + ..... + u.D n +1v.

..............(4)

From (4) we see that if the theorem is true for any value of n, it is also true for the next value of n. But
we have already seen that the theorem is true for n =1.Hence is must be true for n =2 and so for n =3,
and so on. Thus the Leibnitz's theorem is true for all positive integral values of n.
Example. Find the nth differential coefficients of

(i) sin ax cos bx,


(ii) log[(ax + b)(cx + d )].
Solution.

1
1
(i) Let y = sin ax cos bx = [2sin ax cos bx] = [2sin(a + b) x + sin(a b) x].
2
2
1

we know that D n sin(ax + b) = a n sin ax + b + n .


2

1
1
1

y n = (a + b) n sin (a + b) x + n + (a b) n sin (a b) x + n .
2
2
2

(ii) Let y = log [ (ax + b)(cx + d ) ] = log(ax + b) + log(cx + d ).


We know that D n log(ax + b) = (1) n 1 (n 1)!a n (ax + b) n
yn = (1) n 1 (n 1)!a n (ax + b) n + (1) n 1 (n 1)!c n (cx + d ) n
= (1)

n 1

an

cn
+
(n 1)!
.
n
n
+
+
(
ax
b
)
(
cx
d
)

Example. Find the nth derivatives of

1
.
1 5x + 6x2

Solution.

1
1
.
=
6 x 2 5 x + 1 (2 x 1)(3 x 1)
1
A
B
A(3 x 1) + B (2 x 1)
,
2

(2 x 1)(3 x 1)
6 x 5 x + 1 2 x 1 3x 1
1
1
B
Putting x = ,1 = , i.e. B = 3 ; putting x = , A = 2.
2
3
2
2
3
Hence y =
+
= 2(2 x 1) 1 3(3 x 1) 1
2 x 1 3x 1
dn
dx
1
Therefor yn = n 2(2 x 1) n 3(3 x 1) 1
dx
dx
Now we apply the formula,
Let y =

D n (ax + b) 1 = (1) n (n !)(ax + b) n 1 a n .


Hence y n = 2.2n (1) n (n !)(2 x 1) n 1 3.3n (1) n (n !)(3 x 1) n 1 .
or

2n +1
3n +1
yn = (1) (n !)
.
+
n +1
n +1

x
x
(2
1)
(3
1)

1 /2

Example. If y = sin ax + cos ax, prove that y = a 1 + (1) sin 2ax


n

Let y = sin ax + cos ax, then


1
1

yn = a n sin ax + n + a n cos ax + n
2
2

1
1

n
= a sin ax + n + cos ax + n
2
2

1 /2

1/ 2

1
1

= a 1 + 2sin ax + n cos ax + n
2
2

= a n [1 + sin(2ax + n )]1 / 2 = [1 + sin n cos 2ax + cos n sin 2ax]1/ 2


n

[ Q sin n = 0 and cos n = (1) n ]

yn = a n [1 + (1) n sin 2ax]1/ 2

d 2 p a 2b2
= 3 .
Example. If p = a cos + b sin , prove that p +
2
p
d
2

Solution.

Given p 2 = a 2 cos 2 + b 2 sin 2


Differentiating both sides of (1) w.r.t , we get

...(1)

dp
2
2
2p
= 2(b a ) cos sin
d
Again differentiating both sides of (2) w.r.t , we get

...(2)

d 2 p dp
2
2
2
2
p 2 +
= (b a )(cos sin )
d d
Multiplying (3) by p 2 and substituting the value of

...(3)
dp
form (1) and (3), we get
d

d2 p
p 2 + (b 2 a 2 ) 2 cos 2 sin 2 = p 2 (b 2 a 2 )(cos 2 sin 2 )
d
3

d2 p
or p 2 = (a 2 cos 2 + b 2 sin 2 )(b 2 a 2 )(cos2 sin 2 ) (b 2 a 2 )2 cos 2 sin 2
d
3

d2 p
or p 4 + p 3 2 = (b 2 a 2 )[(cos 2 sin 2 )(a 2 cos 2 + b 2 sin 2 ) (b 2 a 2 ) cos 2 sin 2 ]
d
+ (a 2 cos 2 b 2 sin 2 ) 2
=(b 2 a 2 )[(a 2 cos 4 b 2 sin 4 ) + (a 2 cos 2 + b 2 sin 2 ) 2
=b 2 a 2 (cos 2 + sin 2 ) = a 2 b 2
d 2 p a 2b2
p+ 2 = 3 .
p
d
Example. Find yn if y = x n 1 log x.
Hence

Solution.

By Leibnitz's theoram, we get


yn = D n ( x n 1 log x) = D n ( x n 1 ) log x + nD n 1 ( x n 1 ) D log x +

n(n 1) n 2 n 1 2
D ( x ) D log x
2!

n(n 1)(n 2) n 3 n 1 3
D ( x ) D log x + ....... + x n 1 D n Logx.
3!
m!
x m n ; D n x n 1 = 0
Now D n x m =
(m n)!
m!
D n 1 x n 1 = (n 1)!
D n 1 x m =
x m n +1 ;
(m n + 1)!
(n 1)!
(n 1)! 2
D n 2 x n 1 =
x; D n 3 x n 1 =
x
1!
2!
(n 1)!
and D n log x = (1) n 1
xn
Hence
+

1 n(n 1) (n 1)! ! n(n 1)(n 2) (n 1)! 2 2

x 3 + ....
x 2 +
n(n 1)! x + 2!
1!
3!
2!
x
x

yn =
n 1

(n 1)!
n 1 ( 1)
....... + x

xn

(n 1)!
=
[1 {1 n c1 n c2 n c3 + ...... + (1) n +1cn }]
x
(n 1)!
(n 1)!
[1 (1 1) n =
=
x
x

Aliter. y = x n 1 log x

y1 = ( n 1) x n 2 log x + x n 2 .

xy1 = (n 1) x n 1 log x + x n 1 = ( n 1) y + x n 1 .
Differentiating both sides ( n 1)times, we have
D n 2 ( xy1 ) = (n 1) D n 1 y + D n 1 x n 1 .
xyn + (n 1) yn 1 = ( n 1) yn +1 + (n 1)! or yn =

(n 1) !
x

Example.

If

y = a cos(log x) + b sin(log x ), show that x 2 y2 + xy1 + y = 0

and x 2 yn + 2 + (2n 1) xyn +1 + (n 2 + 1) yn = 0.


Solution.

Let y = a cos(log x) + b sin(log x),

1
1
y1 = a sin(log x). + b cos(log x) or xy1 = a sin(log x) + b cos(log x)
x
x
Now again differentiating both sides, we get
1
1
xy2 + y1 = a cos(log x). b sin(log x)
x
x
2
or x y2 + xy1 = [a cos(log x) + b sin(log x)]
or x 2 y2 + xy1 = y
or x 2 y2 + xy1 + y = 0.
Again differentiating both sides in times by Leibnitz's theorem,
D n ( x 2 y2 ) + D n ( xy1 ) + D n ( y ) = 0.
n(n 1) 2 2 n 2
D x D y2 + xD n y1 + nD n +1 y1 + yn = 0
2
+ 2nxyn +1 + n(n 1) yn + xyn +1 + nyn + yn = 0

or x 2 D n y2 +nDx 2 D n 1 y2 +
or x 2 yn + 2

or x 2 yn + 2 + (2n 1) xyn +1 + (n 2 + 1) yn = 0.
Example

If

y = sin(m sin 1 x).

prove

that

(1 x 2 ) y2 xy1 + m 2 y = 0

and

deduce

that

(1 x 2 ) yn + 2 (2n + 1) xyn +1 (n 2 m 2 ) yn = 0.
Solution: Let y = sin(m sin 1 x).

10

y1 = cos(m sin 1 x).

m
(1 x 2 )

or

(1 x 2 ) y12 = m 2 cos 2 (m sin 1 x).

or (1 x 2 ) y12 = m 2 m 2 sin 2 (m sin 1 x) = m 2 m 2 y 2


(1 x 2 ) y12 + m 2 y = m 2 .
Again differentiating both sides, we have
2 y1 y2 (1 x 2 ) 2 xy12 + 2m 2 yy1 = 0. or y2 (1 x 2 ) xy1 + m 2 y = 0.
Now differntiating n time by Leibnitz's theorem, we get
n(n 1)
yn (2) xyn +1 nyn + m 2 yn = 0,
2!
(2n + 1) xyn +1 (n 2 m 2 ) yn = 0.

yn + 2 (1 x 2 ) + nyn +1 (2 x) +
or (1 x 2 ) yn + 2

To find The nth Derivative When x = 0


Example: Find ( yn )0 . if y = sin(a sin 1 x).
Solution:
Let y = sin(a sin 1 x).

y1 = cos(a sin 1 x).

..(1)

a
(1 x )
2

or

y12 (1 x 2 ) = a 2 cos 2 (a sin 1 x) = a 2 a 2 sin 2 (a sin 1 x) = a 2 a 2 y 2

or

y12 (1 x 2 ) + a 2 y 2 a 2 = 0.

................(2)

Differentiating (2), we have


2 y1 y2 (1 x 2 ) y12 (2 x) + 2a 2 yy1 = 0.
or

y2 (1 x 2 ) + xy1 + a 2 y1 = 0

...................(3)

Differentiating (3) n times, we have


n(n 1)
yn + 2 (1 x 2 ) nyn +1 2 x
yn .2 xyn +1 nyn + a 2 yn = 0.
2!
2
or yn + 2 (1 x ) (2n + 1) xyn +1 (n 2 a 2 ) yn = 0.
..................(4)
Putting x = 0 in (1), we get

(y)0 = 0.

Putting x = 0 in (2), we get

(y1)0 = 0

Putting x = 0 in (3), we get

(y2)0 = 0 and

11

Putting x = 0 in (4), we get

( yn + 2 )0 = (n 2 a 2 )( yn )0

Now putting n = 2 in (5),

( y6 )0 = (2 2 a 2 )( y2 )0 = 0.

Putting n = 4 in (5),

( y6 )0 = (42 a 2 )( y4 )0 = 0.

Similarly

( y8 )0 = 0.

Thus the derivatives for which n is even are zero


Again, putting n = 1, ( y3 ) 0 = (1 a ).( y1 ) 0 (1 a )a.
2

Now when n is odd. ( yn + 2 ) 0 = ( n a )( yn ) 0 .


2

Putting n is place of (n-2) we obtain

( yn )0 = ( n 2) 2 a 2 ( yn 2 ) 0
= ( n 2) 2 a 2 (n 4) 2 a 2 (n 6) 2 a 2 ......... 32 a 2 [ y3 ]0
= ( n 2) 2 a 2 (n 4) 2 a 2 ......... 32 a 2 12 a 2 .a.
Example.

If y = tan 1 x, prove that (1 + x 2 ) y2 + 2 xy1 = 0 and deduce that


(1 + x 2 ) yn + 2 + 2( n + 1) xyn +1 + n(n + 1) yn = 0 Hence determine ( yn )0
Solution.

Let y = tan 1 x
1
y1 =
,
(1 + x 2 )
or

(1 + x 2 ) y1 1 = 0.

Differentiating (3), we get

.........(1)
...(2)
...(3)
(1 + x 2 ) y2 + 2 xy1 = 0

.........(4)

Now , differentiating (4) n times by Leibnitz's theorem, we get


n(n 1)
yn .2 + 2 xyn +1 + 2nyn = 0
2!
+ 2(n + 1) xyn +1 + n(n + 1) yn = 0
.........(5)

yn + 2 (1 + x 2 ) + nyn +1 (2 x) +
or (1 + x 2 ) yn + 2

12

Putting x = 0, in (1),(2) and (4), we get


( y )0 = 0, ( y1 )0 = 1, ( y2 )0 = 0.
Also putting x = 0 in (5) we get
( yn + 2 )0 = [ (n + 1)n ] ( yn )0 .

.............(6)

Putting n-2 in place of n in the foumula (6),we get


( yn )0 = [(n 1)(n 2)]( yn 2 )0
= [{(n 1)(n 2)}][{(n 3)(n 4)}]( yn 4 )0
Since from (6), we have (y n-2 )0 = {(n 3)(n 4)}]( yn 4 )0
Case I. When n is even, we have
( yn )0 = [{[(n 1)(n 2)}][{(n 3)(n 4)}]....[(3)(2)]( y2 )0
= 0,

Since ( y2 ) 0 = 0.

Case II. When n is odd, we have


( yn )0 = [{[(n 1)(n 2)][{(n 3)(n 4)}]....[(4)(3)][(2)(1)( y1 )0
= (1)( n 1)2 (n 1)!,

since (y1 )0 = 1.

13

ADDITIONAL PROBLEMS:

1. Find the nth differential coefficient of


(i )
sin 3 x
(ii )

sin x cos 3 x

(iii )

e ax cos 2 x sin x

(iv)

x2
( x + 2 )( 2 x + 3)

2. If

y = eax sin bx, prove that y2 2ay1 + ( a 2 + b 2 ) y = 0

3. If

y = cos ( m sin 1 x ) , prove that (1 x 2 ) y2 xy1 + m 2 y = 0 and

(1 x ) y
2

4. If

n+2

y = ( sin 1 x ) , prove that (1 x 2 ) y2 xy1 2 = 0 and deduce that


2

(1 x ) y
2

5. If

(2n + 1) xyn +1 + (m 2 n 2 ) yn = 0

y = e tan

n+2

(2n + 1) xyn +1 n 2 yn = 0

, prove that (1 + x 2 ) yn + 2 + {2(n + 1) x 1} yn +1 + n(n + 1) yn = 0

14